Relação família-escola no contexto da inclusão escolar de crianças com Transtorno do Espectro Autista - Cabral, Cristiane Soares (Universidade do Vale do Rio dos Sinos, 2014)
The purpose of this dissertation is to investigate the relationship between the family and the school in relation to the process of school inclusion for children with Autism Spectrum Disorder (ASD). The first of the two articles that comprise this study presents a systematic review of the national and international literature on the inclusion of children with ASD, covering the period and the journal of the publishing, the themes investigated, and the methodological choices. The 25 national-based studies, taken from LILACS, BVS, SCIELO and CAPES Portal databases, published between 1998 and 2014 cover the following themes: the school and the process of inclusion of children with ASD, the formation of teachers and their attitude towards the school inclusion, the formation of psychologists and their attitude towards school inclusion, and the inclusion and development of children with ASD in the school context. Additionally, 92 international studies, located in the EBSCOhost and Medline databases, published between 1993 and 2013, were considered. The studies were grouped by investigation theme as follows: the school and the school inclusion process, development and behavior of teachers faced with school inclusion, evaluation instruments for the teaching-learning process in the context of school inclusion, interventions for social inclusion and development of learning, family and the process of school inclusion, inclusion and development of children with ASD in the school context. In terms of methodological aspects, most of the studies located are characterized as empirical and of a qualitative approach. The second study looks into the relationship between the family of a child with ASD and the regular school, the relationship between the family of a child with ASD and the female teacher, and the relationship between the female teacher and the child with ASD. It is a qualitative research, exploratory and transversal in nature, in which mothers, fathers and teachers of four children with ASD diagnose participated. Both mothers and fathers responded the Family Socio-demographic Data Questionnaire and the Autism Spectrum Disorder Data Sheet and an interview about the school inclusion of their child with ASD. The teachers were interviewed about their work with children with ASD. The content analysis showed that the relationship between the parents, the teachers and the school is often triggered by a problem situation involving the child in the school context. It was also observed that few schools exchange information and knowledge with parents on a systematic basis. It is hoped that both studies will contribute as a source of theoretical and empirical information to education and health professionals working with the inclusion of children with ASD so that they will reflect on, and improve their practices resulting in a closer relationship between the family and the school with better development of those children.
Keywords: School inclusion; Family-school relationship; Children; Autism Spectrum Disorder (ASD); Relação família-escola; Criança; Transtorno do Espectro Autista (TEA); Inclusão escolar; ACCNPQ::Ciências Humanas::Psicologia